Makna Tanda Berdasarkan Objeknya dalam Novel Bidadari Berbisik Karya Asma Nadia (Tinjauan Semiotika) Charles Sanders Peirce - Gurusinga, Novita Aurora (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The novel Whispering Bidadari is the work of Asma Nadia (Writer of Mastera). This novel tells the story of the lives of twins who have different characters and have to be separated by a distance to achieve their dream of making their family happy. There are a number of unique indicators in this novel, each having a specific meaning depending on the sociocultural context. Interesting things in this novel, such as strong female characters, religious symbols, and social themes appear in a number of social movement events in real life. Using qualitative descriptive techniques, this research aims to analyze the meaning of signs by applying semiotic theory to the form of icons, indices and symbols in the novel Bidadari Berbisa. Note-taking, reading, and documentation are used to collect data. Charles Sanders Peirce's semiotic theory is used in this research to analyze the meaning of signs and determine what signs are included in it. Multi-iconic aspects, multi-index aspects, and multiple interpretations of signs in symbolic aspects are the results of this research. For example, symbols, indexes and icons in the novel Whispering Bidadari by Asma Nadia. For example, the sign